Fin whale (Balaenoptera physalus) target strength measurements. Issue 3 (15th April 2013) - Bernasconi, Matteo; Patel, Ruben; Nøttestad, Leif; Brierley, Andrew S.
Abstract Active acoustic techniques can be used to detect whales. The ability to detect whales from a moving vessel or stationary buoy could reduce conflicts between hazardous human activities and whales, enabling implementation of mitigation procedures. In order to identify acoustic targets correctly as whales, knowledge of whale target strength (TS) is required. Active acoustic detections of fin whales (Balaenoptera physalus) were made in the Norwegian Sea; acoustic data were collected using calibrated omnidirectional sonar, operating at a discrete frequency of 110 kHz. Three fin whales of similar size (estimated between 16 and 18 m total length) had an overall average TS for all insonified body aspects of −11.4 dB [95% CI −12.05, −10.8] at 110 kHz, with a total spread of nearly 14 dB. As expected, the received signals were stronger when the fin whales were insonified at broadside (−5.6 dB). Individual fin whale TS varied by approximately 12 dB, probably due to variation in lung volume with breathing, and to dynamic swimming kinematics. Our TS values are consistent with values reported previously for other large whales. All data together pave the way for development of automated acoustic whale detection protocols that could aid whale conservation.